2014
DOI: 10.5152/jarem.2014.454
|View full text |Cite
|
Sign up to set email alerts
|

Are Thyroid Functions Changing in Patients with Exacerbated COPD?

Abstract: Objective: Non-thyroidal illness syndrome (NTIS) can be induced by chronic obstructive airway disease (COPD) exacerbation. The aim of this study was to evaluate the thyroid function impairments and the presence of thyroid antibodies in exacerbated COPD patients and to demonstrate the probable relationship with other clinical and biochemical parameters, such as the parameters of arterial blood gases, urea, creatinine, prothrombine time (PT), activated partial prothrombine time (APTT), and international normaliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…in 2014 conducted a study and 21 patients within the exacerbation period of COPD were evaluated and found that 7 (33.33%) patients had free T3 levels below the normal values, and 3 (14.28%) patients had TSH levels below the normal values. [ 16 ]…”
Section: Discussionmentioning
confidence: 99%
“…in 2014 conducted a study and 21 patients within the exacerbation period of COPD were evaluated and found that 7 (33.33%) patients had free T3 levels below the normal values, and 3 (14.28%) patients had TSH levels below the normal values. [ 16 ]…”
Section: Discussionmentioning
confidence: 99%